Comparison of Antioxidant Activity of Basil Herbal Extract (Ocimum sanctum L.): Maceration Vs Reflux Using DPPH Method - Martina E Maleke; AM Muslihin (Jurnal EduHealth, 2026)
Free radicals can trigger oxidative stress that contributes to various health disorders, so that effective and safe natural antioxidant sources are needed. Basil leaves (Ocimum sanctum L.) are known to contain secondary metabolite compounds such as flavonoids and phenolics that have the potential as antioxidants. This study aims to compare the antioxidant activity of basil herbal extracts obtained through maceration and reflux methods and determine the extraction method that produces optimal activity. This study used a quantitative experimental approach. Basil herbal simplicia was extracted with 96% ethanol solvent using maceration and reflux methods, then tested for antioxidant activity by the DPPH (2,2-diphenyl-1-picrylhydrazyl) method using UV-Vis spectrophotometry at a wavelength of 514 nm. The parameter observed was the IC50 value as an indicator of the strength of antioxidant activity. The results showed that the maceration extract had an IC50 value of 64.54 ppm, while the reflux extract was 115.37 ppm, where the maceration extract was categorized as strong and the reflux extract was categorized as moderate. The macerated extract showed higher antioxidant activity than the reflux extract. Therefore, the extraction method influences the antioxidant activity of basil leaves, and maceration is recommended to produce extracts with optimal antioxidant potential. These findings support the use of basil leaves as a natural source of antioxidants in the development of health and pharmaceutical products.